Risk-assessment-based approach to patients exposed to endoscopes contaminated with Pseudomonas spp. Issue 1 (May 2015) - Robertson, P.; Smith, A.; Mead, A.; Smith, I.; Khanna, N.; Wright, P.; Joannidis, P.; Boyd, S.; Anderson, M.; Hamilton, A.; Shaw, D.; Stewart, A.
Summary Patients exposed to bronchoscopes contaminated with Pseudomonas aeruginosa are at increased risk of pseudomonal infection. The optimal methods for management and mitigation of risk following exposure are controversial. This article describes a two-phase risk assessment following pseudomonal contamination of a family of 75 endoscopes, detected through routine surveillance and attributed to one endoscope washer-disinfector. An initial risk assessment identified 18 endoscopes as high risk, based on the presence of lumens used for irrigation or biopsy. Exposure was communicated to the patients' clinical teams and a further clinical risk assessment of the exposed patients was performed. No patients developed complications due to pseudomonal infection.